Penerapan Sanksi Atas Pelanggaran Hukum Disiplin Militer Dalam Sistem Peradilan Militer - Salmanita Shalsabella Pramudita; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This court is regulated in Law Number 31 of 1997 concerning military justice, so that if a soldier commits a violation of the law, he will be subject to the court. As the author, I took the title: